Duodenal cholinergic tuft cell number is increased in functional dyspepsia. Issue 10 (6th April 2022) - Huang, Xinyi; Oshima, Tadayuki; Akiba, Yasutada; Yoshimoto, Takanori; Chen, Junji; Taki, Masato; Tomita, Toshihiko; Fukui, Hirokazu; Kaunitz, Jonathan D.; Miwa, Hiroto
Abstract: Background: Low‐grade duodenal inflammation has recently been identified in patients with functional dyspepsia (FD). Chemosensory tuft cells were reported to be associated with gastrointestinal diseases. We therefore assessed duodenal tuft cell density and microinflammation in patients with FD to determine whether these measures could serve as useful biomarkers, and also correlated tuft cell density and microinflammation in FD patients. Methods: Duodenal biopsy specimens were obtained from patients with FD and from controls. Tuft cells, eosinophils, and mast cells were immunochemically stained with specific antibodies. Tuft cells were identified by immunostaining for doublecortin‐like kinase 1 (DCLK1); cholinergic tuft cells were assessed by double staining for choline acetyltransferase (ChAT) and DCLK1. Immune‐type tuft cells were assessed by IL‐25 mRNA expression using real‐time PCR. Key Results: The density of intramucosal eosinophils and mast cells was significantly higher in the duodenum of FD patients than in controls. The density of tuft cells was significantly higher in the duodenum of FD patients compared with controls, and significantly correlated with eosinophil density in the duodenum of FD patients and controls. Moreover, a fraction of ChAT‐positive cells was DCLK1 positive; all duodenal DCLK1+ tuft cells were ChAT‐immunoreactive in FD and in control subjects. Conclusions and Inferences: Cholinergic tuft cell density was higher in the duodenum of patients with FD and significantly correlated with eosinophil density. Further studies are needed to investigate the pathophysiological significance of tuft cells in FD and may provide valuable clues to the pathophysiology of FD. Abstract : Cholinergic tuft cell density was higher in the duodenum of patients with FD and significantly correlated with eosinophil density. This may indicate that tuft cell influences FD pathogenesis, with consequent dyspeptic manifestations.